2016
DOI: 10.1021/acs.chemrestox.6b00016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics Reactivation of Nrf2 in Prostate TRAMP C1 Cells by Curcumin Analogue FN1

Abstract: It has previously been demonstrated that curcumin is effective against prostate cancer growth and progression in TRAMP mice, potentially acting through the epigenetic modification of the Nrf2 gene and the subsequent induction of the Nrf2-mediated anti-oxidative stress cellular defense pathway. FN1 is a synthetic curcumin analog that shows stronger anti-cancer activity than curcumin. The purpose of this study was to investigate a potential epigenetic effect of FN1 that restores Nrf2 gene expression in TRAMP-C1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Not surprisingly, previous studies also proved that Nrf2 plays a key role in the development of cancers [2830], including prostate cancer [19, 31]. It seems that an increased expression of Nrf2 may suppress the proliferation and invasion abilities of prostate cancer cells [19, 32], which exactly agreed with the results of our present study. However, Raatikainen et al revealed that when the Nrf2 was increased, the biochemical recurrence-free survival would be shortened and the overall survival rate would be worse, indicating a worse prognosis of prostate cancer patients and enhanced proliferative and invasive abilities [33].…”
Section: Discussionsupporting
confidence: 93%
“…Not surprisingly, previous studies also proved that Nrf2 plays a key role in the development of cancers [2830], including prostate cancer [19, 31]. It seems that an increased expression of Nrf2 may suppress the proliferation and invasion abilities of prostate cancer cells [19, 32], which exactly agreed with the results of our present study. However, Raatikainen et al revealed that when the Nrf2 was increased, the biochemical recurrence-free survival would be shortened and the overall survival rate would be worse, indicating a worse prognosis of prostate cancer patients and enhanced proliferative and invasive abilities [33].…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown to inhibit cell proliferation, cell survival and the production of several cytokines by altering the function of numerous important regulatory pathways, such as NFκB [21] and the transcription factor NRF2 Keap1 [22]. Moreover, Curcumin targets several different proteins and inhibit the activity of various kinases in vitro [23], as well as the activity of histone acetyl transferases [24], therefore, curcumin alters different signaling pathways and also effects epigenetic control of gene expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Nrf2 accumulates, and then, translocates to the nucleus, where it targets a cis-acting antioxidant response element, which activates a set of genes. In addition to p62, the Nrf2/Keap1 signalling axis is regulated by epigenetic mechanisms that involve microRNAs1819. To date, numerous microRNAs have been identified that function as modulators of Nrf2 and related regulatory proteins2021.…”
mentioning
confidence: 99%